Biomass formation and nutrient partitioning in potted longan trees under partial rootzone drying - Srikasetsarakul U. (2014)
In northern Thailand Dimocarpus longan (Lour.) is the most important fruit crop grown. With the fruit growing and maturing during the dry season, irrigation is needed to ensure a high yield. With the increase in use of production irrigation, water is becoming scarcer. In a previous study it was documented that under "partial rootzone drying" (PRD) water use efficiency (WUE) can be increased. The reason has so far not been researched. In this study, ten split-root longan trees were irrigated in PRD and compared to ten trees which received water on both sides of the root. Biomass formation, leaf area and nutrient concentration (N, P, K) in roots, shoots and leaves were analyzed. It was shown that the biomass formed under PRD was significantly less than under normal irrigation. The leaf size was lower under PRD and the roots were not well developed. The P and K content in all parts of the PRD treated trees was less, while the N content was not significantly lower. This study shows that under PRD, less biomass is produced than under full irrigation. In combination with other results which show no yield reduction, it can be concluded that longan trees under stress reduce their vegetative, but not their generative growth.